VILLAGE GOVERNMENT FINANCIAL PERFORMANCE USING VALUE FOR MONEY ANALYSIS - Wibowo, Agoes Hari Edy; Fitriani, Fitriani; Evi Safitriani, (Journal of Innovation Research and Knowledge, 2023)
The public sector is an important aspect of governance in dealing with economy in the future. Including the smallest category of village accounting as a public sector application that also needs to be considered. The public sector has demands to carry out of accountability of public funds. In assessing the performance of village governance through the village revenue and expenditure budget, it can become a village overview to realize good governance. Performance appraisal uses the measurement of value for money, the authors emphasize the measurement of the economy, effiency and effectiveness. The purpose of this study was to determine the application of value for money measurement in APBDes in assessing the financial performance of the village governments (case study in Bojonggaok Village Jamanis Sub District of Tasikmalaya District). The method used is descriptive quantitative. From the results of the study using the measurement of value for money, it can be concluded that the financial performance of the village government has not been optimal and keep trying to improved its performance. Judging from the average In terms of economy for three years from 2019-2021 it is in the economic category. In terms of efficiency from years 2019-2021 is efficient. In terms of effectiveness from years 2019-2021 are quite effective.